Incompatibility in Podospora anserina: Comparative Properties of the Antagonistic Cytoplasmic Factors of a Nonallelic System - Labarère, Jacques (J Bacteriol, 1974)
In the fungus Podospora anserina, the interaction between the nonallelic incompatible R and V genes has two consequences: a lytic reaction due to the synthesis of specific proteolytic enzymes, and a quenching in protein and ribonucleic acid synthesis. The incompatibility reaction when vegetative or sexual R and V cells fuse is asymmetric: it is induced only in the R protoplasm. The cessation in ribonucleic acid and protein synthesis was investigated in heterokaryotic strains carrying the antagonistic R and V genes and their “neutral” r and v alleles. Asymmetry between R and V genes lies in the fact that the strains homozygous for the R genes are the only strains that cannot grow. From these results it is postulated that the V-gene product is a diffusible cytoplasmic factor and that the R-gene product, which is nonautonomous, is a ribosomal component.